Platinum-based hydroxide composite aerogel material as well as preparation method and application thereof

By growing hydroxides in situ on the surface of platinum-based hollow spheres and forming chain-shaped platinum-based hollow spheres/hydroxide composite aerogel materials, the problem of slow hydrolysis kinetics of platinum under alkaline conditions and the influence of active agents in traditional preparation is solved, and an efficient and stable alkaline hydrogen evolution electrocatalytic effect is achieved.

CN119663361APending Publication Date: 2025-03-21ZHENGZHOU FOGUANG ELECTRIC POWER EQUIPMENT CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411935222.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, the hydrolysis kinetics of platinum under alkaline conditions are slow, and the surfactants and capping agents used in traditional preparation will affect the catalytic performance, resulting in stability and efficiency problems of platinum-based hydrogen evolution electrocatalysts in industrial applications.

Method used

By preparing a platinum shell/non-precious transition metal core hydrogel precursor, the non-precious transition metal element is precipitated from the core by using the hydrothermal method and converted into hydroxide in situ on the surface of the platinum-based hollow sphere to form a chain-shaped platinum-based hollow sphere/hydroxide composite aerogel material. This method does not require colloid stabilizers and capping agents, has strong structural stability and high platinum atom utilization rate.

Benefits of technology

It realizes high-efficiency electrocatalytic hydrogen evolution in alkaline media, significantly improving the utilization rate of platinum atoms and hydrolysis rate, while maintaining the stability of the catalyst, making it suitable for industrial mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a chain platinum-based hollow sphere / hydroxide composite aerogel material and a preparation method and application thereof, and the preparation method comprises the following steps: mixing a non-noble transition metal salt solution and a sodium borohydride aqueous solution for reduction reaction to obtain a non-noble transition metal nanoparticle suspension; then adding a platinum salt solution into the suspension to obtain a platinum shell / non-noble transition metal core hydrogel precursor; and transferring the precursor into a reaction kettle containing a precipitator, carrying out hydrothermal reaction treatment, and finally washing and freeze-drying the obtained product, thereby obtaining the product. The preparation method can be completed in a water system without using a colloid stabilizer and / or an end-capping reagent, and is very simple in process, easy to operate in the process and suitable for industrial batch production. The composite material integrates the three-dimensional continuous conductive network structure of the metal aerogel, the efficient water dissociation capability of the hydroxide and the high atom utilization rate of the porous hollow spheres, and shows excellent water electrolysis hydrogen production activity and stability in an alkaline medium.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of synthesis of nano materials, and in particular relates to a chain platinum-based hollow sphere / hydroxide composite aerogel material and a preparation method and application thereof. Background Art

[0002] As a clean, renewable, high calorific value, carbon-free energy, hydrogen energy has gradually become an important medium for solving the energy crisis, building the future energy system, and realizing energy transformation. The main challenge facing the large-scale application of the hydrogen energy industry is how to produce hydrogen efficiently and economically. Electrocatalytic water splitting driven by renewable electricity (such as wind or solar energy) is considered to be a sustainable and efficient hydrogen production technology. In particular, the hydrogen evolution reaction in alkaline media is more in line with the actual industrial production requirements and has high product purity, which is highly favored. The key to realizing this technology is to develop economical, efficient and stable alkaline hydrogen evolution electrocatalysts. Platinum is widely regarded as the most effective electrocatalyst material. However, the high cost of platinum and its slow water dissociation rate under alkaline conditions greatly hinder its large-scale application in industrial hydrogen production electrolyzers. Therefore, how to develop and design high-performance low-platinum-based alkaline hydrogen evolution electrocatalysts is crucial for large-scale industrial hydrogen production.

[0003] In order to further reduce the amount of platinum used, a common strategy is to introduce highly open nanostructures, such as platinum-based hollow spheres and nanoframes, to maximize the utilization of platinum atoms and improve catalytic performance. In particular, platinum-based hollow spheres composed of ultrathin porous walls can fully expose the inner and outer surfaces, which can greatly improve the utilization of platinum atoms and have received widespread attention in the field of electrocatalysis. In addition, in order to address the problem of slow water dissociation kinetics of platinum under alkaline conditions, interface engineering is usually used to construct platinum / hydroxide heterostructures. In this type of hybrid material, hydroxide can promote the breaking of H-OH bonds and produce active hydrogen (H*), which then combines on the platinum surface and releases hydrogen, thereby improving the hydrogen evolution reaction kinetics of platinum in alkaline media. However, there are still several problems to be solved in the preparation of platinum / hydroxide heterostructures. First, most hydroxides currently achieve nucleation and growth on the platinum surface through surface adsorption, van der Waals forces or electrostatic interactions, but the heterogeneous interface bonding force obtained is weak and usually does not have long-term durability; secondly, the traditional preparation process usually uses surfactants or capping agents. These organic species are usually strongly adsorbed on the surface of the nanostructure, which will mask the active sites of the catalyst and seriously affect its catalytic performance. In addition, it is still a major challenge to develop platinum-based alkaline hydrogen evolution catalysts with high platinum atom utilization, accelerated water dissociation rate and high stability by integrating platinum structural morphology regulation (such as hollow spheres) and hydroxide heterogeneous interface construction.

[0004] This application was developed based on this. Summary of the invention

[0005] In order to solve the above problems existing in the prior art, the present invention aims to provide a chain platinum-based hollow sphere / hydroxide composite aerogel material. The composite aerogel material realizes the epitaxial in-situ growth of hydroxide on the surface of platinum-based hollow spheres for the first time, has strong structural stability, and integrates the structural advantages of metal aerogels and porous hollow spheres, thereby greatly improving the utilization rate of platinum atoms and the water dissociation rate, and showing excellent electrocatalytic hydrogen evolution activity and stability in alkaline media.

[0006] The present invention also provides a method for preparing the above-mentioned chain-like platinum-based hollow sphere / hydroxide composite aerogel material. The method prepares a platinum shell / non-precious transition metal core hydrogel precursor, utilizes a hydrothermal method and a precipitant to precipitate the non-precious transition metal element from the inner core, and converts it into hydroxide in situ on the surface of the formed platinum-based hollow sphere in a manner similar to epitaxial growth, thereby obtaining a platinum-based hollow sphere / hydroxide composite aerogel catalyst material having a chain structure. The present invention can be completed in a water system without using a colloidal stabilizer and / or a capping agent, the process is very simple, the process is easy to operate, and it is suitable for industrial mass production.

[0007] The present invention also provides the use of the above-mentioned chain-like platinum-based hollow sphere / hydroxide composite aerogel material in electrolyzing water to produce hydrogen in an alkaline medium.

[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing a platinum-based hydroxide composite aerogel material comprises the following steps: S1, mixing a non-noble transition metal salt solution and a sodium borohydride aqueous solution to perform a stirring reduction reaction to obtain a non-noble transition metal nanoparticle suspension; S2, adding the platinum salt solution to the suspension obtained in step S1 and continuously stirring the reaction (stirring is required for about 5-20 minutes) to obtain a platinum shell / non-noble transition metal core hydrogel precursor; S3, mixing the precursor obtained in step S2 with a precipitant and subjecting the mixture to a hydrothermal reaction, and finally washing and freeze-drying the obtained product.

[0009] Specifically, in step S1, the non-precious transition metal salt includes but is not limited to one or more combinations of nickel nitrate, nickel chloride, nickel sulfate, cobalt nitrate, cobalt sulfate, cobalt chloride, ferric nitrate, ferric sulfate, ferric chloride, etc. Further preferably, the concentration of the non-precious transition metal salt can be 0.18-0.36 mM, the concentration of the sodium borohydride aqueous solution can be 20-120 mM, and the stirring reaction time is 2-35 min.

[0010] Furthermore, the molar ratio of the non-noble transition metal salt to sodium borohydride may be 1:1-7.

[0011] Specifically, in step S2, the platinum salt includes but is not limited to one of chloroplatinic acid, potassium chloroplatinate, sodium chloroplatinate, etc.

[0012] Furthermore, the molar ratio of the platinum salt to the non-noble transition metal may be 1:4-12.

[0013] Specifically, in step S3, the precipitant includes but is not limited to one of potassium hydroxide, sodium hydroxide, urea, etc. Further preferably, the concentration of the precipitant can be 5-12 mM.

[0014] Furthermore, the molar ratio of the non-noble transition metal salt to the precipitant may be 1:2-11.

[0015] Furthermore, in step S3, the temperature of the hydrothermal reaction can be 100-180° C., and the time of the hydrothermal reaction can be 6-12 hours.

[0016] The present invention provides a platinum-based hydroxide composite aerogel material prepared by the above-mentioned preparation method. The specific surface area of ​​the composite aerogel material is 50 to 150 m 2 / g, hydroxide nanosheets grow on the surface of platinum-based hollow spheres, the size of the hollow spheres is 10 to 25 nm, and they are linked to each other to form a three-dimensional network structure.

[0017] The present invention also provides the use of the platinum-based hydroxide composite aerogel material in electrolyzing water to produce hydrogen in an alkaline medium.

[0018] Compared with the prior art, the advantages and technical progress of the technical solution of the present invention are: (1) The present invention can be completed in a water system without the use of a colloidal stabilizer and / or a capping agent, so the surface of the obtained chain-like platinum-based hollow sphere / hydroxide composite aerogel material is clean and the active sites are fully exposed. In addition, the process is very simple and easy to operate, and is suitable for industrial mass production.

[0019] (2) The present invention first prepares a platinum shell / non-precious transition metal core hydrogel precursor, and uses a hydrothermal method and a precipitant to precipitate the non-precious transition metal element from the core, so that it is in situ converted into hydroxide on the surface of the formed platinum-based hollow sphere in a manner similar to epitaxial growth. Therefore, the bonding force between the platinum-based hollow sphere and the hydroxide is strong, and it has good structural stability. The composite material integrates the three-dimensional continuous conductive network structure of the metal aerogel, the efficient water dissociation ability of the hydroxide and the high atomic utilization rate of the porous hollow sphere, and exhibits excellent activity and stability in hydrogen production by electrolysis of water in alkaline media.

[0020] (3) The composite material obtained by the present invention is the first to integrate the advantages of hydroxide, hollow spheres and metal aerogels, accelerating the water dissociation rate while improving the utilization rate of platinum atoms, and showing excellent electrocatalytic hydrogen evolution activity and stability in alkaline media. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a digital photo of the chain-like platinum-nickel hollow sphere / nickel hydroxide composite aerogel material prepared in Example 1 of the present invention; Figure 2 The scanning electron microscope image (left) and the transmission electron microscope image (right) of the chain-like platinum-nickel hollow sphere / nickel hydroxide composite aerogel material prepared in Example 1 of the present invention; Figure 3 This is the nitrogen physical adsorption isotherm of the chain-like platinum-nickel hollow sphere / nickel hydroxide composite aerogel material prepared in Example 1 of the present invention; Figure 4 This is a comparison chart of hydrogen evolution performance of the chain-like platinum-nickel hollow sphere / nickel hydroxide composite aerogel material prepared in Example 1 of the present invention, commercial platinum-carbon, nickel hydroxide nanosheet aerogel in Comparative Example 1, and chain-like platinum-nickel hollow sphere aerogel in Comparative Example 2. DETAILED DESCRIPTION

[0022] In order to better explain the present invention and facilitate understanding, the technical solution of the present invention is further described in detail below in conjunction with embodiments and drawings, but the protection scope of the present invention is not limited thereto.

[0023] In the following examples, unless otherwise specified, all raw materials used are common commercially available products that can be directly purchased.

[0024] In the examples, if the temperature is not specifically mentioned, it is generally assumed to be room temperature (25±5°C).

[0025] Example 1 A method for preparing a chain-like platinum-nickel hollow sphere / nickel hydroxide composite aerogel material, the specific preparation steps are as follows: S1, adding 5 mL of 20 mM sodium borohydride aqueous solution to 500 mL of 0.18 mM nickel chloride aqueous solution, stirring and reacting for 10 min to obtain a nickel nanoparticle suspension; S2, adding 30 uL of 0.75M chloroplatinic acid solution to the suspension obtained in step S1, and stirring the mixture for 10 min to obtain a platinum shell / nickel core hydrogel precursor; S3, the precursor obtained in step S2 was transferred to a 70 mL reactor containing 5 mM potassium hydroxide aqueous solution for hydrothermal reaction treatment, the hydrothermal reaction temperature was 100°C, and the reaction time was 6 hours. Finally, the obtained product was washed with water and freeze-dried (-2°C for 24 hours, the same below) to obtain a chain-like platinum-nickel hollow sphere / nickel hydroxide composite aerogel material.

[0026] Example 2 A method for preparing a chain-like platinum-nickel hollow sphere / nickel hydroxide composite aerogel material, the specific preparation steps are as follows: S1. Add 5 mL of 50 mM sodium borohydride aqueous solution to 500 mL of 0.28 mM nickel chloride aqueous solution, and stir for 10 min to obtain a nickel nanoparticle suspension.

[0027] S2, adding 30 uL of 0.75M chloroplatinic acid solution to the suspension obtained in step S1, and stirring continuously for 10 minutes to obtain a platinum shell / nickel core hydrogel precursor; S3, transferring the precursor obtained in step S2 to a 70 mL reactor containing 7.5 mM urea aqueous solution for hydrothermal treatment, the hydrothermal reaction temperature is 150° C., and the reaction time is 8 h. Finally, the obtained product is washed with water and freeze-dried to obtain a chain-like platinum-nickel hollow sphere / nickel hydroxide composite aerogel material.

[0028] Example 3 A method for preparing a chain-like platinum-nickel hollow sphere / nickel-cobalt hydroxide composite aerogel material, the specific preparation steps are as follows: S1. Add 5 mL of 70 mM sodium borohydride aqueous solution to 500 mL of a mixed aqueous solution of nickel chloride and cobalt chloride, wherein the total concentration of nickel and cobalt is 0.36 mM. After stirring for 10 min, a nickel-cobalt alloy nanoparticle suspension is obtained.

[0029] S2, adding 30 uL of 0.75M potassium chloroplatinate solution to the suspension obtained in step S1, and stirring the mixture for 10 min to obtain a platinum shell / nickel-cobalt alloy core hydrogel precursor; S3, the precursor obtained in step S2 is transferred to a 70mL reactor containing 9.5mM sodium hydroxide aqueous solution for hydrothermal treatment, the hydrothermal reaction temperature is 180°C, and the reaction time is 12h. Finally, the obtained product is washed with water and freeze-dried to obtain a chain-like platinum nickel cobalt hollow sphere / nickel cobalt hydroxide composite aerogel material.

[0030] Example 4 A method for preparing a chain-like platinum-iron hollow sphere / iron hydroxide composite aerogel material, the specific preparation steps are as follows: S1. Add 5 mL of 120 mM sodium borohydride aqueous solution to 500 mL of 0.36 mM ferric chloride aqueous solution, and stir for 35 min to obtain an iron nanoparticle suspension.

[0031] S2, adding 30uL of 0.75M sodium chloroplatinate solution to the suspension obtained in step S1, and stirring continuously for 10min to obtain a platinum shell / iron core hydrogel precursor; S3, the precursor obtained in step S2 is transferred to a 70mL reactor containing 12mM sodium hydroxide aqueous solution for hydrothermal treatment, the hydrothermal reaction temperature is 180°C, and the reaction time is 12h. Finally, the obtained product is washed with water and freeze-dried to obtain a chain-like platinum iron hollow sphere / iron hydroxide composite aerogel material.

[0032] Comparative Example 1 In order to compare the performance, a nickel hydroxide aerogel material without chain-like platinum-based hollow spheres was prepared in this comparative example. The preparation method thereof was basically the same as the preparation method of the chain-like platinum-based hollow sphere / hydroxide composite aerogel material of the above Example 1, except that no platinum salt solution was added.

[0033] Comparative Example 2 In order to compare the performance, a chain platinum-nickel hollow sphere aerogel material without hydroxide was prepared in this comparative example. The preparation method thereof was basically the same as the preparation method of the chain platinum-based hollow sphere / hydroxide composite aerogel material of the above Example 1, except that no precipitant was added during the hydrothermal reaction.

[0034] Performance Testing 1. Figure 1 The digital photo of the chain-like platinum-nickel hollow sphere / nickel hydroxide composite aerogel material obtained in Example 1 is given, and its scanning electron microscope image and transmission electron microscope image are shown in FIG. Figure 2 As shown. Figure 1 , 2 It can be seen that it has a three-dimensional continuous conductive network skeleton and a multi-level pore structure. A careful observation shows that the skeleton of the composite material is constructed by a string of hollow spheres with an average diameter of 11.8±1.9nm. Nickel hydroxide nanosheets are evenly attached to the surface of the strings of platinum nickel hollow spheres. Figure 3 The nitrogen physical adsorption isotherm of the chain-like platinum nickel hollow sphere / nickel hydroxide composite aerogel material prepared in Example 1 is given; Figure 3 As shown in Figure 2, the specific surface area of ​​the composite material is approximately 150 m 2 / g.

[0035] 2. The test results of the specific surface areas of the products prepared in the other embodiments and comparative examples are shown in Table 1. As can be seen from Table 1, the specific surface areas of the composite aerogel materials prepared in Examples 1 to 4 of the present invention are relatively large, much higher than those in Comparative Examples 1 and 2, and the higher specific surface areas can provide more abundant active sites.

[0036] Table 1 Specific surface area of ​​products in different embodiments 3. Hydrogen evolution performance test of the chain-like platinum-nickel hollow sphere / nickel hydroxide composite aerogel material prepared in Example 1: 1mL of anhydrous ethanol was added to 20uL of Nafion solution (5wt%) and mixed evenly; 1mg of chain-like platinum-nickel hollow sphere / nickel hydroxide composite aerogel material was weighed and placed in the mixed solution, and ultrasonically dispersed for 60 minutes to obtain a uniform suspension. 30μL of the suspension was placed on a rotating disk electrode with a diameter of 5mm and dried at 40℃ for 1h. The obtained rotating disk electrode was the working electrode, the graphite electrode was the counter electrode, and the silver / silver chloride electrode was the reference electrode. The electrodes were all relative to the reversible hydrogen electrode (E(RHE)=E(Ag / AgCI)+0.210V+0.059×pH), and the electrolyte was 1mo1 / L KOH. The electrocatalytic activity of the chain-like platinum-nickel hollow sphere / nickel hydroxide composite aerogel material for alkaline hydrogen evolution reaction was determined.

[0037] Taking electrocatalytic hydrogen evolution as an example, the chain-like platinum-nickel hollow sphere / nickel hydroxide composite aerogel material of the present invention is 10 mA / cm 2 The overpotential at Figure 4 As shown in Figure 2), the current density at 50 mV is 56.32 mA / cm 2 , while the current density of commercial carbon-supported platinum, comparative example 1 and comparative example 2 is only 12.2 mA / cm 2 , 6.5mA / cm 2 and 31.3mA / cm 2 , which are 4.6 times, 8.6 times and 1.8 times of the current density, respectively, indicating that the composite aerogel material synthesized by the method of the present invention has higher electrocatalytic hydrogen evolution activity.

[0038] Obviously, the above embodiments of the present invention are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all implementation methods here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a platinum-based hydroxide composite aerogel material, characterized in that: The steps include: S1, mixing a non-noble transition metal salt solution with a sodium borohydride aqueous solution to perform a reduction reaction to obtain a non-noble transition metal nanoparticle suspension; S2, adding a platinum salt solution to the suspension obtained in step S1 to react and obtain a platinum shell / non-noble transition metal core hydrogel precursor; S3, mixing the precursor obtained in step S2 with a precipitant and subjecting the mixture to a hydrothermal reaction, and finally washing and freeze-drying the obtained product.

2. The method for preparing the platinum-based hydroxide composite aerogel material according to claim 1, characterized in that: In step S1, the non-precious transition metal salt is one or more combinations of nickel nitrate, nickel chloride, nickel sulfate, cobalt nitrate, cobalt sulfate, cobalt chloride, ferric nitrate, ferric sulfate, and ferric chloride.

3. The method for preparing a platinum-based hydroxide composite aerogel material according to claim 2, characterized in that: The molar ratio of the non-noble transition metal salt to sodium borohydride is 1:1-7.

4. The method for preparing the platinum-based hydroxide composite aerogel material according to claim 1, characterized in that: In step S2, the platinum salt is one of chloroplatinic acid, potassium chloroplatinate and sodium chloroplatinate.

5. The method for preparing a platinum-based hydroxide composite aerogel material according to claim 4, characterized in that: The molar ratio of the platinum salt to the non-precious transition metal salt is 1:4-12.

6. The method for preparing the platinum-based hydroxide composite aerogel material according to claim 1, characterized in that: In step S3, the precipitant is one of potassium hydroxide, sodium hydroxide and urea.

7. The method for preparing a platinum-based hydroxide composite aerogel material according to claim 6, characterized in that: The molar ratio of the non-noble transition metal salt to the precipitant is 1:2-11.

8. The method for preparing the platinum-based hydroxide composite aerogel material according to claim 1, characterized in that: In step S3, the temperature of the hydrothermal reaction is 100-180° C., and the time of the hydrothermal reaction is 6-12 hours.

9. A platinum-based hydroxide composite aerogel material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the platinum-based hydroxide composite aerogel material according to claim 10 in producing hydrogen by electrolysis of water in an alkaline medium.